Experimental Taguchi approach and Gray–Taguchi optimization on mechanical properties of aluminum 8011 alloy sheet under uniaxial tensile loads. (2019) - Mahesh Reddy, D.; Anitha Lakshmi, A.; ul Haq, Ahsan
Abstract: Aluminum alloys are making a special consideration for extreme temperature applications in service background of aircraft structures, missile engines, and pressure containers. This creates crucial to recognize various mechanical properties of the Al 8011 alloy such as yield strength (ys), % of elongate and ultimate strength (uts) have been valued by depleting uniaxial tensile loads. The mechanical properties of aluminum alloy materials are purely reliant on the rate at which the part is heated and quenched. The tensile experiments are accompanied at 150 °C and 450 °C with different strain conditions (0.1 s −1, 0.001 s −1 ) to find the material behavior of Al 8011 alloy sheet. The Taguchi orthogonal array and the (S/N) signal to noise ratio are used to analyze the effect of elected process considerations and their levels.